2015
DOI: 10.1371/journal.pgen.1004976
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants Modulating CRIPTO Serum Levels Identified by Genome-Wide Association Study in Cilento Isolates

Abstract: Cripto, the founding member of the EGF-CFC genes, plays an essential role in embryo development and is involved in cancer progression. Cripto is a GPI-anchored protein that can interact with various components of multiple signaling pathways, such as TGF-β, Wnt and MAPK, driving different processes, among them epithelial-mesenchymal transition, cell proliferation, and stem cell renewal. Cripto protein can also be cleaved and released outside the cell in a soluble and still active form. Cripto is not significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 82 publications
2
8
0
Order By: Relevance
“…However, given the limited number of MPM patients recruited in the present study, this result should be carefully evaluated and more work involving additional cohorts is needed to elucidate the prognostic role of the rs2235503. Then, we assessed whether the performance of SMRP could be improved when taking into account the subjects' genetic background, in agreement with previous findings for other biomarkers (Cramer et al, 2003;Gudmundsson et al, 2010;Enroth et al, 2014;Ruggiero et al, 2015;Wang et al, 2018). Notably, we found that the AUC for individuals carrying the rs2235503-C/C genotype was higher (0.915) than that of carriers of the A-allele (0.798) and higher as compared to the whole population (0.877).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, given the limited number of MPM patients recruited in the present study, this result should be carefully evaluated and more work involving additional cohorts is needed to elucidate the prognostic role of the rs2235503. Then, we assessed whether the performance of SMRP could be improved when taking into account the subjects' genetic background, in agreement with previous findings for other biomarkers (Cramer et al, 2003;Gudmundsson et al, 2010;Enroth et al, 2014;Ruggiero et al, 2015;Wang et al, 2018). Notably, we found that the AUC for individuals carrying the rs2235503-C/C genotype was higher (0.915) than that of carriers of the A-allele (0.798) and higher as compared to the whole population (0.877).…”
Section: Discussionsupporting
confidence: 83%
“…However, we believe that the genetic background could play a prominent role in this context. An increasing number of studies, by showing the importance of genetic variations in altering the concentration and the accuracy of several biomarkers, strongly support this idea (Cramer et al, 2003;Gudmundsson et al, 2010;Enroth et al, 2014;Ruggiero et al, 2015;Wang et al, 2018). Furthermore, we showed for the first time that single nucleotide polymorphisms (SNPs) located within the 3 -UTR of the MSLN gene could affect the SMRP levels through a miRNA-mediated mechanism (Garritano et al, 2014).…”
Section: Introductionmentioning
confidence: 58%
“…When challenged with a colon-specific carcinogen, Cripto heterozygous mice exhibited a higher incidence of colon cancer compared to Cripto wild-type mice [111]. Polymorphisms and mutations in the TDGF1 locus have been linked to different medical conditions and assessing the TDGF1 genetic status was shown to improve cancer patients' risk stratification, as well as produce information about potential genetic disorders [2,112,113]. For instance, Cripto promoter methylation was shown to discriminate among different subtypes of testicular germ cell tumors [112].…”
Section: Cripto In Experimental Medical Research: Therapeutic and Tramentioning
confidence: 99%
“…However, its use as a pan-cancer serological marker should be further investigated in order to establish a definite threshold for baseline levels of circulating Cripto. In this regard, a few polymorphisms in the TDGF1 promoter have been linked to a significantly reduced level of circulating Cripto in a genome-wide association study of about 1500 individuals [113].…”
Section: Cripto In Experimental Medical Research: Therapeutic and Tramentioning
confidence: 99%
“…Additionally, soluble Cripto-1 levels are elevated in the plasma obtained from colon, lung, glioblastoma, and BC patients, what suggests that Cripto-1 levels in human plasma or serum may have potential clinical diagnostic and prognostic significance [ 7 ]. A genome-wide association study for Cripto-1 serum levels performed in an isolated human population, aiming to identify genetic variants associated with the levels of circulating Cripto-1 protein in the serum, confirmed its fundamental role in embryonic development and cancer [ 66 ]. Moreover, GRP78/BIP is expressed on the surface of tumor cells [ 67 ] where it preferentially binds to GPI-anchored proteins [ 68 ], and it has been shown that Cripto-1/GRP78/BIP complex increases tumor growth [ 69 ].…”
Section: Cripto-1 Notch/csl and Wnt/β-catenin Signaling Pathways Armentioning
confidence: 99%